2011
DOI: 10.1590/s0102-33062011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura arbórea da Floresta Ombrófila Densa Altomontana de serras do Sul do Brasil

Abstract: 1 RESUMO(Estrutura arbórea da Floresta Ombrófi la Densa Altomontana de serras do Sul do Brasil). O presente trabalho teve os objetivos de agrupar informações sobre a estrutura arbórea da fl oresta altomontana da Serra do Mar paranaense e de compará-las com as de fl orestas altomontanas de outras serras do Sul e Sudeste do Brasil. Foram realizados levantamentos fi tossociológicos em diversas montanhas de quatro importantes serras (ou subserras) do Paraná. Nas quatro subserras foram amostrados 2294 indivíduos (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
2
9
0
19
Order By: Relevance
“…The families Myrtaceae, Aquifoliaceae, and Lauraceae have also been shown to be highly representative of the structure of upper montane cloud forests in the state of Paraná, Brazil (Scheer et al 2011). In the upper montane cloud forest at Camanducaia, which, like our study area, is at an elevation of 1900 m, França & Stehmann (2004) found that the richest families were Myrtaceae, Solanaceae, Lauraceae, Rubiaceae, Symplocaceae, and Asteraceae.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The families Myrtaceae, Aquifoliaceae, and Lauraceae have also been shown to be highly representative of the structure of upper montane cloud forests in the state of Paraná, Brazil (Scheer et al 2011). In the upper montane cloud forest at Camanducaia, which, like our study area, is at an elevation of 1900 m, França & Stehmann (2004) found that the richest families were Myrtaceae, Solanaceae, Lauraceae, Rubiaceae, Symplocaceae, and Asteraceae.…”
Section: Discussionsupporting
confidence: 60%
“…In the upper montane cloud forest at Bocaina de Minas, where the elevation ranges from 1210 m to 1360 m, Carvalho et al (2005) found Melastomataceae and Myrtaceae to be the richest families, followed by Fabaceae, Lauraceae, Annonaceae, Solanaceae, Euphorbiaceae, Asteraceae, Cyatheaceae, and Rubiaceae. Other authors have also identified Myrtaceae as the richest family in montane forests within the Atlantic Forest Biome of Brazil, including other forests in the Serra da Mantiqueira (Pereira et al 2006;França & Stehmann, 2004;Meirelles et al 2008), as well as in other regions of the country, including the south (Scheer et al 2011) and southeast (Oliveira-Filho & Fontes 2000;Costa et al 2011). Conversely, the family Fabaceae was not found in our study area, and its absence at higher elevations has also been noted in other studies (Oliveira-Filho & Fontes, 2000;Gentry 1995;França & Stehmann, 2004;Meireles et al 2008;Scheer et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Gêneros neotropicais, austral-antárticos e pantropicais, indicadores de formações florestais de altitude, como Chusquea, Drimys, Ilex e Weinmannia estiveram presentes no estrato arbóreo da Floresta Altimontana em Monte Verde (Giulietti & Pirani 1987;Gentry 1995;Hamilton et al 1995). Abutilon, Escallonia, Macropeplus, Myrceugenia e Symplocos são outros gêneros arbóreos neotropicais, austral-antárticos ou pantropicais com espécies restritas e indicadoras de florestas altimontanas das Regiões Sul ou Sudeste brasileiros (Meireles et al 2008;Scheer et al 2011). Baccharis, Gaylussacia, Leandra, Mimosa, Salvia, Senecio e Tibouchina são gêneros arbustivos com uma elevada riqueza e um número representativo de espécies endêmicas em formações altimontanas (Meireles 2009;Mocochinski & Scheer 2008).…”
Section: Distribuição Geográficaunclassified
“…Myrceugenia destacou-se como um gênero muito rico e dominante nas florestas altimontanas da porção sul da Floresta Atlântica (Klein 1960;Meireles et al 2008;Scheer et al 2011). Muitas das espécies brasileiras desse gênero ocorrem preferencialmente nas regiões planálticas da costa leste brasileira, em altitudes superiores a 900-1000 metros, e são espécies indicadoras das florestas altimontanas sob climas frios e úmidos (Landrum 1981;Meireles et al 2008;Meireles 2009 …”
Section: Distribuição Geográficaunclassified
See 1 more Smart Citation